Betel quid, chewing habits and difficult intubation: A case report and critical appraisal of evidence for practice - Narendra, P. L. (Anesth Essays Res, 2015)
Betel quid is used by 10–20% of world of population. Oral submucus fibrosis (OSF) is a chronic premalignant disease common in South Asian countries where betel quid is chewed. It is characterized by juxtaepithelial fibrosis of oral cavity and limited mouth opening, which can cause difficult intubation. A recent study in Taiwan has revealed long-term betel nut chewing is not predictor of difficult intubation. We describe two cases of OSF and critically analyze this study and its implications for clinical practice. OSF is now seen in Saudi Arabia and western countries with use of commercial betel quid substitutes. Although betel quid without tobacco is used in Taiwan, available evidence suggests rapid and early development of OSF where commercial chewing products like Pan Masala are used in India. Effects of betel quid may vary depending on the composition of quid and chewing habits. Studies where personal habits are involved must be analyzed carefully for external validity. Even though, Taiwan study is controlled, its validity outside Taiwan is highly questionable. Since OSF can cause unanticipated difficult intubation, thus during preanesthetic assessment, history of betel quid chewing, more importantly use of commercial chewing products is more likely to give clues to severity of OSF and possible difficult intubation. Further controlled trails in populations where commercial chewing products are used is necessary to detect association of chewing habits and difficult intubation.